(untitled) (KULT_online, 2012)
With a revitalization of antique philosophical questions about the purpose of education, Kirsten Meyer opens in her habilitation treatise places for a systematical discussion, which deals with a fundamental consideration of aims and ’measures’ of education instead of determinations of educational tools. Here she encounters explosive and intellectually challenging topics of autonomy, equality of opportunity, human rights and neutrality of the state. The leading thesis, which considers different contemporary Anglo-American philosophical discourses, is that the philosophy of education can’t do other than think about the question of a good life in a normative ’impregnation’.